Pengaruh Intellectual Capital, Risiko Operasional, Debt To Equity Ratio, dan Non Performing Loan Terhadap Kinerja Keuangan Pada Perusahaan Bank Buku IV yang Terdaftar di Bursa Efek Indonesia - Yayu Kusdiana (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
This research was conducted at Bank Buku IV companies listed on the Indonesia Stock Exchange. This study aims to determine the effect of intellectual capital, operational risk, debt to equity ratio, and non-performing loans on financial performance. This research uses quantitative methods. The data used is secondary data. The sampling technique used purposive sampling technique with a sample of 5 Bank Buku IV companies from the period 2017 to 2020. The analysis used was panel data regression with the Eviews version 12 computer application program. performance, debt to equity ratio and non-performing loan have no significant effect on financial performance, only operational risk has a significant negative effect on financial performance. Through the f test, it is known that simultaneously intellectual capital, operational risk, debt to equity ratio and non-performing loan have a significant effect on financial performance.